The Relationship Between Adherence to Taking Iron Supplement Tablets and Complications in Mothers - Rani Safitri; Nurjanah Abubakar; Rosyidah Alfitri (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Iron deficiency anemia remains a significant health issue among pregnant women in Indonesia and is one of the contributing factors to high maternal and infant mortality rates. The prevalence of iron deficiency anemia in Indonesia has reached 50.5%. According to data from the 2010 National Health Survey, the anemia rate among pregnant women was 40.1%. Anemia during pregnancy increases the risk of low birth weight (LBW) babies, bleeding before and during labor, and can even lead to maternal and neonatal death. The purpose of this study was to determine the relationship between adherence to iron supplement tablet consumption and complications during labor and in neonates. This research used an analytic observational method with a retrospective cohort approach. The study involved 56 maternity mothers who met the inclusion and exclusion criteria, selected through purposive sampling. Data were analyzed using the Fisher's exact test. The results of the cross-tabulation between compliance with iron supplement tablet (TTD) consumption and maternal complications showed a p-value of 0.387 (p > 0.05), while the relationship between TTD compliance and neonatal complications showed a p-value of 0.681 (p > 0.05). It can be concluded that there is no significant relationship between adherence to iron supplement tablet consumption and the occurrence of maternal or neonatal complications.